Talking about competition? Discursive shifts in the economic imaginary of competition in public debates - Stephan Pühringer; Laura Porak; Johanna Rath (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2021)
In this paper, we apply a discourse analytical framework to explore the performativity of the economic concept of competition in public policy discourses. We focus on the role of professional economists as opinion leaders to analyze how concepts of competition have entered public discourses. The main economic imaginary ascribes to competition the function of a primary mode for economic and social coordination, ensuring prosperity and wealth. Competitiveness is predominately interpreted not as a means but an end in itself. Furthermore, three partly conflicting discursive positions on how competition should be organized arise in the discourse: first, the neoliberal position interprets every non-efficient market outcome as the result of institutional intervention, hindering effective competition; second, the ordoliberal position of fair competition evaluates governance intervention positively, as long as they promote the functioning of competition; third, the Keynesian position promotes corrected competition, i.e. diverse policy intervention to compensate for market failure outcomes.
Keywords: 330; competition; competitiveness; media debates; consulting; economic experts; critical discourse analysis